The imagined island : history, identity, & utopia in Hispaniola - San Miguel, Pedro Luis (University of North Carolina Press, 2005)
National identity in Haiti and the Dominican Republic.
"Originally published in Spanish with the title La isla imaginada: historia, identidad y utopía en la Espanõla"--Title page verso.
Translated from the Spanish.
Keywords: Bosch, Juan, -- 1909-2001.; Bosch, Juan, -- 1909-; Bosch, Juan, -- 1909-2001; Dominican Republic -- Historiography.; Haiti -- Historiography.; Haiti -- Foreign public opinion, Dominican.; Intellectuals -- Dominican Republic -- Attitudes.; Public opinion -- Dominican Republic.; Hispaniola -- Race relations.; Politics and literature.; Literature and history.; Intellectuels -- République dominicaine -- Attitudes.; Opinion publique -- République dominicaine.; Politique et littérature.; Littérature et histoire.; République dominicaine -- Historiographie.; Haïti -- Historiographie.; Haïti -- Opinion publique dominicaine.; Hispaniola -- Relations raciales.; HISTORY -- General.; Historiography; Intellectuals -- Attitudes; Literature and history; Politics and literature; Public opinion; Race relations; Dominican Republic; Haiti; Hispaniola; Geschichtsschreibung